Pro Telerik ASP.NET and Silverlight Controls - Paz, José Rolando Guay (2012)
ASP.NET and Silverlight are powerful platforms that allow developers to build rich and sophisticated web systems. One of the most important features is xtensibility. While it provides, out of the box, a whole set of controls that enables developers to create web applications, they are very basic controls. This is where Telerik comes in. Telerik is a company that provides a set of controls targeting ASP.NET and Silverlight which empower the developer with the ichness of their features, allowing them to take the web applications to the next level.